Is happiness possible during the war: an analysis of value shifts on student essay materials = Czy szczęście jest możliwe podczas wojny: analiza zmian wartości na materiałach esejowych dla studentów - Kutyrova, Vira (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article analyses the dynamics of the value of happiness during war. The article is based on the material of students` biographical essays, as well as on the results of the World Values Study. The author considers happiness as a value construct which manifests itself in a high degree of personal satisfaction with one`s activities, conditions and lifestyle, in positive emotions of joy. Citing the results of the World Values Study, the author argues that the positive dynamics of happiness in the Ukrainian society over the past decades is an important indicator of the update of the value of self-expression among Ukrainians. It is difficult to say whether this trend will continue now, as war updates survival values.
Keywords: happiness; biographical essays; values of survival and self-realization; war; trauma; szczęście; esej biograficzny; wartości przetrwania i samorealizacji; wojna